The Influence of Internal Control Systems on The Accountability of APBDes Management in Lemahsugih District Majalengka Regency - Rahman, Erpi; Sulistiani, Sulistiani; Kurniawan, Ryan Feryana (LPPM Universitas Sebelas April, 2025)
This study aims to determine the influence of internal control systems on the accountability of APBDes management in Lemahsugih district Majalengka Regency. This study uses a quantitative approach as a research method. This study uses primary data obtained through questionnaires. The sampling method applied in this study is purposive sampling. The number of samples used in this study is 75 respondents. Data analysis was conducted using various methods, including descriptive statistical analysis, normality test, linearity test, heteroscedasticity test, simple linear regression analysis, t-test, as well as testing for correlation coefficient, and determination coefficient. The results of this study obtained a regression coefficient value of 0.621 or 62.1%. The calculated t-value of 6.638 is greater than the table t-value of 1.993, and the significance value of 0.000 is less than 0.05. Therefore, it can be concluded that there is an effect of the internal control system on the accountability of APBDes management in Lemahsugih District Majalengka Regency. The magnitude of this effect is reflected in determination coefficient value of 0.376 or 37.6%. This means that the internal control system has an influence on the accountability of APBDes management in Lemahsugih District, Majalengka Regency by 37.6%. The remaining 62.4% is influenced by other variables not examined in this study. Thus, a strong internal control system helps to improve the accountability of APBDes management.